Selectivity of Leguminous Trees by Water Buffaloes in Semi-intensive Systems - Galloso-Hernández, Maykel Andrés; Rodríguez-Estévez, Vicente; Alvarez-Díaz, Carlos Armando; Soca-Perez, Mildrey; Dublin, Devon Ronald; Iglesias-Gómez, Jesús; Guelmes, Leonel Simon (Frontiers in Veterinary Science, 2020)
Water buffaloes (Bubalus bubalis) manifest different levels of selectivity for different pastures and forages. Knowledge of feed selectivity is important to facilitate the design of efficient production systems which take into account optimal animal welfare. In this study, the selectivity of nine 18-month old water buffalo females for Leucaena leucocephala, Albizia lebbeck, Gliricidia sepium and Moringa oleifera was evaluated. After 12 hours of grazing Megathyrsus maximum, the animals were housed in individual shelters and 1.2 kg of leaves from each of the four tree species were offered to the animals simultaneously. The selectivity, measured as the intake of dry mater (DM), was highest for A. lebbeck (mean=0.34 kgDM SD= 0.05 kg), followed by L. leucocephala (mean = 0.30 kgDM, SD = 0.03 kg) M. oleifera (mean = 0.11 kgDM, SD = 0.05 kg) and G. sepium (mean =0.10 kgDM, SD = 0.02 kg) (P <0.01). The crude protein intake was highest for A. lebbeck and L. leucocephala. Notably, the less selected leaves were those of G. sepium and M. oleifera. This study suggests that the inclusion of A. lebbeck and L. leucocephala in silvopastoral systems may increase both the consumption and well-being of water buffaloes in the tropics.